Making Decisions and Motor Actions with Technical Biomechanical Classifications in Male Judo Weight Categories - Aedo-Munoz, E (Sciendo, 2020)
The aim of the study was to compare motor action variables of judo combat phases and technical biomechanical assessment of the seven weight categories. The sample was composed of 638 bouts (176 of extra lightweight <66 kg, 289 of half lightweight 66 > 73 kg, 180 of lightweight 73 > 81 kg, 244 of half middleweight 81 > 90 kg, 174 of middleweight 81 > 90 kg, 151 of half heavyweight 90 > 100 kg and 142 of heavyweight >100 kg) during motor actions of approach, gripping, attack, defense and groundwork combat phases, verifying the interactions between them by Markov chains and comparisons by Kruskall-Wallis and Dunn post hoc tests (p ≤.05). The results demonstrated that lighter weight categories showed higher approach phases than the heavyweight category, and the lightweight group demonstrated higher defensive action frequencies than the half lightweight category and heavyweight athletes. Heavyweight and middleweight categories demonstrated higher groundwork combat frequencies than lighter weights, and the heavyweight category showed higher pause frequencies than the lightweight category. Regarding the decision-making model, the main transitions presented by the Markov chains showed higher prevalence of the following combinations: gripping occurring before the lever and length attacks, lever attack followed by the length attack, and length attack occurring earlier than the groundwork phase. © 2020 Dany Alexis Sobarzo Soto, Esteban Aedo-Muñoz, Ciro José Brito, Suzi Camey, Bianca Miarka, published by Sciendo 2020.